Enhanced phonon resonance by non-uniform surface nanopillars in Si nanowires. (15th May 2023) - Liu, Haofei; Li, Weikang; Cao, Zengqiang; Huang, Xiaoyu; Ni, Yuxiang
Highlights: Non-uniform nanopillars induce stronger phonon resonance effect in Si nanowire. The distance between two adjacent nanopillars does not affect the phonon propagation. Phonon localization occurs due to the disorder induced by non-uniform pillars. Abstract: Based on the wave nature of phonons, the lattice thermal conductivity of nanowires can be regulated by phonon resonators such as surface nanopillars. In this study, the impact of the height and distance of the resonant nanopillars on the thermal conductivity of Si nanowires were investigated. The results calculated from the molecular dynamics simulations show that with increasing height of the nanopillars, the corresponding thermal conductivity decreases. We found that the nanopillars with non-uniform heights induce stronger phonon resonance effect and can further suppress the thermal conductivity, as compared to the models with nanopillars of uniform heights. On the other hand, changing the distance between two adjacent nanopillars does not obviously affect the phonon propagation. Phonon dispersion relations show the formation of flat bands, which confirms the occurrence of phonon resonances due to the nanopillars. When the heights of the nanopillars become non-uniform, more flat bands were generated, and the phonon group velocity further decreased. Analyses of phonon participation ratio indicate stronger phonon localization induced by the disorder stemming from the non-uniform nanopillar height. Our investigation yields new insights into the physical mechanisms governing heat transport in nanowires with phonon resonators, and thus opens potential new routes to the design of thermoelectric devices.